89.8k views
3 votes
Look at image...........

Look at image...........-example-1
User Reis
by
5.3k points

2 Answers

4 votes

Answer:

your answer would be B

Step-by-step explanation:

User Anthonycr
by
5.1k points
3 votes

Answer:

Explanation:

2x + 3y = 6

y = x/3 - 3

Since the second equation is already solved for y, we can easily use the substitution method.

Substitute y in the first equation with x/3 - 3

2x + 3(x/3 - 3) = 6

2x + x - 9 = 6

3x = 15

x = 5

Now use the second equation, and x = 5, to solve for y.

y = x/3 - 3

y = 5/3 - 3 = 5/3 - 9/3

y = -4/3

Answer: (5, -4/3)

User Monish Khatri
by
5.3k points